Perbandingan penilaian senyum yang estetis menggunakan konsep Golden Proportion, Recurring Esthetic Dental (RED), dan Golden Percentage - Ayu Ratih Utari Mayun, I Gusti (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background : Various studies have shown that facial aesthetics is determine by the harmonization and aesthetic teeth. One important aspect of aesthetic dentistry focuses on improving the appearance especially the rehabilitation of the maxillary anterior teeth. There are several concepts in aesthetic dentistry that can be use as a guideline in determining the shape and size of the maxillary anterior teeth to get the harmonization of aesthetic smile and function of the teeth, such as Golden Proportion, Reccuring Esthetic Dental (RED) dan Golden Percentage. Golden Proportion was the first and most often used as a guideline in determining the proportion of the frontal width maxillary anterior teeth. But it has some weaknesses, therefor an alternative concept was developed, such as Recurring Esthetic Dental (RED) and Golden Percentage. Recurring Esthetic Dental (RED) is the proportion of the successive of the frontal width of the maxillary anterior teeth remaining constant, when progressing distally from the midline. While Golden Percentage is the percentage proportion of the frontal width of maxillary anterior teeth should be 10%, 15%, 25%, 25%, 15%, 10%. Summary : The proportion of the width of the maxillary anterior teeth are unsuitable with the concept of the Golden Proportion, Recurring Esthetic Dental (RED) and Golden Percentage. But the concept of Golden Percentage assessed more applicable in its use.